Management of plant species for controlling pests, by peasant farmers at Lagoa Seca, Paraíba state, Brazil: an ethnoecological approach - Mourão José; Guimarães Andréia (BMC, 2006)
Abstract Ethnoecological knowledge may be understood as spontaneous knowledge, culturally referenced of any society's members, learned and transmitted through social interactions and that are targeted at resolution of daily routine situations. The traditional knowledge in small scale economy societies as well as the non-academic knowledge in urban-industrial societies might be included in this concept. An ethnoecological approach study was performed here on people living at the communities of Alvinho, Almeida, Chã do Marinho, Floriano, and Chã de Oiti, all located in the municipality of Lagoa Seca, Paraíba state, Northeast Brazil. The general objective pursued here was to study the knowledge that peasant farmers have on management of plant species utilized for pest control. For this, the methodological instruments employed here to investigate the ethnoecological knowledge were: direct observation, structured and semi-structured interviews, and tours conducted by local peasant farmers. We analyzed the data obtained under an emic/etic view and also by comparing the local knowledge with those obtained from the literature. The results showed that people in those communities utilize management alternatives for controlling pests, which are mainly: (i) fallowing; (ii) crop rotation; (iii) destruction of crop remains and fruits attacked by pests; (iv) alternations of crops with repellent plants; and/or (v) mixed cropping; (vi) insect's larvae covered with soil; (vii) crops irrigated abundantly; and (viii) soil preparation. The recovery and comprehension we get about this knowledge as well as the farmers' savoir faire, are extremely important to the revival of ancient agricultural practices, which have been forgotten due to advances in modern agriculture. The data obtained here showed that a huge body of knowledge the farmers have on many forms or strategies of management are generally compatible with scientific knowledge.